Entrance Botanic Garden - (:unkn) unknown (My University, 2009)
A picture of three men on various mode of transportation near the entrance on the Botanical Gardens. The first man is standing on the Pitch Walk, the second is riding a bicycle and the third is riding a donkey.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Cycling--Trinidad and Tobago